2015
DOI: 10.1021/acs.jpcc.5b07520
|View full text |Cite
|
Sign up to set email alerts
|

Organosoluble Au102(SPh)44 Nanomolecules: Synthesis, Isolation, Compositional Assignment, Core Conversion, Optical Spectroscopy, Electrochemistry, and Theoretical Analysis

Abstract: Characterization of p-mercaptobenzoic acid (p-MBA) protected Au102(p-MBA)44 nanomolecules has been so far limited by its water-soluble ligand system. In this work we report the first synthesis and isolation of thiolate-protected organosoluble Au102(SPh-X)44 nanomolecules via one-phase synthesis. Monodispersity of the nanomolecules was confirmed from matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS), and composition was determined from high-resolution electrospray ionization mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…[32][33][34] Among the variously proposed mechanisms of cytotoxicity,t he one involving in the release of silver ions from Ag NPsh as received mosta ttention; [35][36][37][38][39] however,i tr equires furtherv alidation, as evidenceo fr eleased silver ions is far from sufficient (especially for thiolated Ag NPs). [40][41][42] Based on our findings,w ed emonstrate that DPV can be used for the rapid and preliminary evaluation of the cytotoxicity of thiolated Ag NPs. [40][41][42] Based on our findings,w ed emonstrate that DPV can be used for the rapid and preliminary evaluation of the cytotoxicity of thiolated Ag NPs.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…[32][33][34] Among the variously proposed mechanisms of cytotoxicity,t he one involving in the release of silver ions from Ag NPsh as received mosta ttention; [35][36][37][38][39] however,i tr equires furtherv alidation, as evidenceo fr eleased silver ions is far from sufficient (especially for thiolated Ag NPs). [40][41][42] Based on our findings,w ed emonstrate that DPV can be used for the rapid and preliminary evaluation of the cytotoxicity of thiolated Ag NPs. [40][41][42] Based on our findings,w ed emonstrate that DPV can be used for the rapid and preliminary evaluation of the cytotoxicity of thiolated Ag NPs.…”
mentioning
confidence: 74%
“…[38,39] Herein, we provide such evidenceb yu sing differential pulse voltammetry (DPV), am ethodw hichh as been widely used in the metal nanoclusters field. [40][41][42] Based on our findings,w ed emonstrate that DPV can be used for the rapid and preliminary evaluation of the cytotoxicity of thiolated Ag NPs. Furthermore, we reveal that the cytotoxicity of thiolatedA gN Ps is size dependent in the investigated size range.Initially,t he Ag 14 SG 11 (where, SG = l-reduced glutathiolate) (Ag 14 for short) nanoclustersa nd approximately 8nmn anoparticles [43] were employed as the model nanoparticles for this study.C haracterization of silver ions released from Ag NPs by using mass spectrometry is challenging, owing to the interference of the fragmentation of silver nanoclusters or silver nanocrystals( see FigureS1).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…This is expected as the surface availability of the nanomolecule decreases as the size increases steric effect by para -tert-butyl groups becomes significant compared to smaller core-size Au 36 (SR) 24 . Similarly, it was found that physicochemical differences between thiophenol, 4-methoxybenzene thiol, 4-methylbenzene thiol, and 4-bromobenzene thiol are subtle and results in same composition of AuNMs (Nimmala and Dass, 2014 ; Chen et al, 2015a ; Rambukwella et al, 2015 ; Rambukwella and Dass, 2017 ). Although, Au 36 (SR) 24 NMs system was reported (Das et al, 2014 ) with bulky cyclopentane thiol, exclusive formation of Au 36 (SR) 24 is dominated by electronic effect by aromatic nature of the ligand rather than steric effect.…”
Section: Ligand Effect Demonstrated By Direct Synthesismentioning
confidence: 93%
“…8,9,17 A set of eleven ligands, included in experimental or theoretical reports devoted to the study of thiolated gold clusters, is considered along this study. The first set of eight achiral ligands includes para-mercaptobenzoic acid (p-MBA), 18 SPh, 19,20 SPhNO 2 , 21 cyclohexanethiol (S-c-C 6 H 11 ), 1,22,23 2-phenylethylthiolate (2-PET), 24 mercaptopropionic acid (MPA that has been considered in gold nanoparticles), 25 besides the amply used SCH 3 ligand during calculations. Starting from the experimental Au 18 cluster protected by 14 S-c-C 6 H 11 ligands, a set of initial structures was built; some of them are depicted in Fig.…”
mentioning
confidence: 99%